Evaluation of Postoperative Articulation Function of Oral Cancer Patients - Miyakura, Tsuyoshi; Iwaki, Hiroshi; Amagasa, Teruo; Kuwabara, Kazumichi; Hasegawa, Kazuki; Negishi, Akihide; Yamashiro, Masashi; Nagasawa, Hirokazu; Kobayashi, Junji; Isii, Junichi; Yoshimasu, Hidemi; Suzuki, Tetsuo (Journal of Japanese Society of Oral Oncology, 1999)
The purpose of this study was to standardize the methods for evaluation of postoperative articulatory function. Japanese monosyllable intelligibility and conversation intelligibility were examined in 113 oral cancer patients, and patient's own assessment was also carried out by a questionnaire given to 74 patients. These three methods are relatively simple and easy and have been available for assessment of speech function. 1) Monosyllable intelligibility is variable, depending on the number of syllables. In case of moderate and severe speech disorders, the results of 25 syllables intelligibility test were considerably lower than those of 100 syllables. On the other hand, 67 syllables intelligibility tended to be slightly higher than those of 100 syllables in all degrees of disorder. 2) In case of mild disorder, the correlation between syllable intelligibility and conversation intelligibility was not significant. Conversation intelligibility with a finer scale is desirable in case of mild disorder. 3) Patient's own assessment (subjective evaluation) did not agree with conversation intelligibility (objective evaluation) . The patients had a tendency to underestimate their own speech function.